Antidepressant use in pregnancy and severe cardiac malformations: Danish register‐based study. (22nd June 2021) - Kolding, L; Ehrenstein, V; Pedersen, L; Sandager, P; Petersen, OB; Uldbjerg, N; Pedersen, LH
Abstract : Objective: Studies restricted to live births may underestimate severe teratogenic effects. We address the limitation by including data from both prenatal and postnatal diagnoses of cardiac malformations. Design: Register‐based study. Setting: Denmark. Population: 364 012 singleton pregnancies from 2007 to 2014. Methods: We used data from five nationwide registries. Exposure to antidepressants was measured using redeemed prescriptions. Main outcome measures: Pregnancies with cardiac malformations that end in miscarriage, termination, stillbirth, postnatal death or cardiac surgery <1 year of birth were classified as severe cardiac malformations (SCM). Propensity scores with adjusted prevalence ratios (PRs) were calculated. Results: SCM were reported in 972 of 364 012 pregnancies overall and in 16 of 4105 exposed. For venlafaxine, the PR for SCM was 2.13 (95% confidence interval [CI] 0.89–5.13), 1.73 (95% CI 1.08–2.77) for other cardiac malformations, and there was a cluster of hypoplastic left heart syndromes (HLHS) (crude PR 17.4 [95% CI 6.41–47.2]), none of which ended in a live birth. For HLHS, the absolute risk increase was 4.4/1000 and the number needed to harm was 225. For selective serotonin reuptake inhibitors, the PRs were 1.09 (95% CI 0.52–2.30) and 1.38 (95% CI 1.00–1.92) for SCM and other cardiac malformations, respectively. Conclusions: Pregnancy exposure to venlafaxine is associated with an increased risk of severe cardiac malformations but with a low absolute risk. Potential mechanisms include direct effects or confounding by indication. Venlafaxine exposure is a marker for risk pregnancies for which fetal echocardiography may be considered. Tweetable abstract: Exposure to venlafaxine is associated with an increased risk of cardiac malformations but with a low absolute risk. Tweetable abstract: Exposure to venlafaxine is associated with an increased risk of cardiac malformations but with a low absolute risk.